Mutual funds and safe government bonds: Do returns matter? - Marco Graziano; Maurizio Michael Habib (European Central Bank (ECB), 2024)
This paper investigates the sensitivity of the demand for safe government debt to currency unhedged and hedged excess returns in a sample of US mutual funds. We find evidence of active rebalancing towards government bonds that offer relatively higher returns on an unhedged basis, in particular euro-denominated securities. The size of the effect is large, leading to a change in portfolio share by around one percentage point on average in response to a change by one percentage point in the currency-specific excess return. Interestingly, mutual funds rebalance their portfolio towards currencies, such as the Japanese yen, that display large deviations in the covered interest parity and offer higher returns than US Treasuries on an hedged basis. Finally, when global financial risk is on the rise, US mutual fund managers repatriate their investments towards US government debt securities, mainly at the expenses of euro-denominated ones. Our results imply that deviations in pricing conditions like uncovered and covered interest parity for sovereign bonds affect capital flows from the United States towards other major currency areas.
Keywords: F3; G11; G12; G15; G23; 330; government bonds; safe assets; mutual funds; search for yield; covered interest parity